The role of glucosinolates of Brassica genus in the crop system - H. Zukalová; J. Vašák; D. Nerad; P. Štranc (Plant, Soil and Environment, 2002)
Glucosinolates with Brassica genus as secondary metabolites have a lot of functions and effects. Glucosinolates form less than 2% of the overall sulphur content at the beginning of vegetation in different parts of the plants and during growth their content is decreasing and forms less than 0.1%. This low representation doubts their storage function. With its chemical composition, they are ranked among natural pesticides with active and passive resistance against diseases and pests. They show repellent effects and properties of natural biofumigators in soil after ploughing in their biomass as green fertilizing, or after ploughing in after harvest the leftovers of rape. The principle of these effects is decomposition products of glucosinolates - bioactive isothiocyanates. Very important from this point of view are turnip rape Rex and Brassica juncea, whose content of these compounds is the highest one and they are resistant against the attack of Ceutorrhynchus pleurostigma. The same effect showed also when attacked by Phoma lingam. With other winter Brassicas either hybrid or linea and summer rape is this defensive system suppressed because of their lowered content due to breeding interferences, leading to limitation of their anti-nutritional negative effects. It is possible to state the final result after finding out the production of the above matter, roots, and after evaluation of the sorbal characteristics of the soil and evaluation of the state of health of the following crop or vegetable. After this overall analysis, it will be possible to evaluate the biofumigation properties of accessible varieties of the Brassica genus.